1998
DOI: 10.3758/bf03206052
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chemical complexity on the perception of multicomponent odor mixtures

Abstract: The present study investigates the hypothesis that complex object odors (odors that emanate from flowers, foods, sewage, etc.) that consist of dozens of odorants are processed and encoded as discrete entities, as if each was a single chemical odor. To test this hypothesis, the capacity of trained subjects to discriminate and identify the components of stimuli consisting of one to eight object odors was determined. The results indicated that subjects could only identify up to four object odors in a mixture, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 42 publications
7
65
0
Order By: Relevance
“…Consistent with mixture suppression, odors of many common foods and fragrances appear to be dominated by notes of single compounds that impart characteristic, albeit crude, identities [20,25,26,61]. Because odor-component identification is suppressed in mixtures [44,45,46], we surmise that olfactory notes originate from very few components that dominate odors of mixtures due to their relative strength at a given point in time [39,56]. "Top note," "middle note" and "bottom note" [62] are terms used to specify the timing of successive odors emerging from fragrant stimulus mixtures.…”
Section: Mixture Component Identification Reveals Analytic Odor Prmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistent with mixture suppression, odors of many common foods and fragrances appear to be dominated by notes of single compounds that impart characteristic, albeit crude, identities [20,25,26,61]. Because odor-component identification is suppressed in mixtures [44,45,46], we surmise that olfactory notes originate from very few components that dominate odors of mixtures due to their relative strength at a given point in time [39,56]. "Top note," "middle note" and "bottom note" [62] are terms used to specify the timing of successive odors emerging from fragrant stimulus mixtures.…”
Section: Mixture Component Identification Reveals Analytic Odor Prmentioning
confidence: 96%
“…However, humans have a quite limited ability to simultaneously identify odor qualities of individual compounds in multi-component mixtures. Component odors in mixtures containing as few as four moderately intense simultaneously presented components cannot be recognized above chance levels [44,45,46]. We hypothesized that rapid selective adaptation, *To whom correspondence should be addressed; e-mail: mfrank@neuron.uchc.edu, telephone: 1-860-679-3354, fax: 1-860-679-4760, Dr. Marion E. Frank, Center for Neurosciences, Oral Health and Diagnostic Sciences, University of Connecticut Health Center, Farmington, CT 06030-1605, USA Author Contributions: All four authors contributed equally.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral studies of odor mixtures in humans [37,42,43] and in animals, including monkeys [38], rats [34,40,56], catfish [54], spiny lobsters [41], and bees [22,51], have focused on testing the discriminability between mixtures and components, or establishing whether single components in mixtures are perceived individually or as a whole. Neurophysiological studies in animals have addressed these questions, and also compared whether responses to mixtures are of the same "type" (i.e., excitatory, suppressive, or nonresponsive) or show the same temporal pattern as responses to the individual components [28,33,52].…”
Section: Introductionmentioning
confidence: 99%
“…Previous olfactory research conducted on evaluating the odor intensity of coffee and heptane has reported b values near 0.5 . The results of this study show that synthetic swine odor has values of b that are comparable to the studies of other odorants Dengel and Koster, 1998;Linden et al, 1998;Livermore and Laing, 1998).…”
Section: Panel and Scale Developmentsupporting
confidence: 74%
“…Odor intensity was measured by the method of direct scaling in reference to an odor standard of defined intensity using three to four trained panelists Liden et al, 1998;Livermore and Laing, 1998). Direct scaling was based on estimation of the intensity of olfactory sensations associated with an odor source by assigning numerical values to sensory stimuli.…”
Section: Evaluation Of the Odor Intensity Associated With Swine Manurmentioning
confidence: 99%